THE IMPACT OF ADDICTIVE BEHAVIOR ON NATIONAL CULTURE AND TRADITIONAL VALUES (Scientific journal of the Fergana State University, 2026)
This article analyzes the formation and various manifestations of addictive behavior among youth. It highlights the negative impact of such behaviors on national culture and traditional values. Particular attention is given to the role of spiritual and moral values, family upbringing, and religious and cultural norms in Uzbek society in preventing addictive behavior. The article also explores the causes of addictive tendencies among young people and discusses the effectiveness of culturally grounded approaches in addressing these issues.